A Survey of Use of Electronic Resources at Narula Institute of Technology Library and Documentation Center - Chandra, Suvra (Journal of Information and Knowledge, 2013)
This article reports the result of a questionnaire survey about e-resources and their use by users of the library and documentation center of Natural Institute of Technology.